2020
DOI: 10.1038/s41390-020-01193-9
|View full text |Cite
|
Sign up to set email alerts
|

Vertical transmission of SARS-CoV-2 from infected pregnant mother to the neonate detected by cord blood real-time polymerase chain reaction (RT-PCR)

Abstract: Vertical transmission of SARS-CoV-2from infected pregnant mother to the neonate detected by cord blood real-time polymerase chain reaction (RT-PCR),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Although initial reports on SARS-CoV-2 vertical transmission found no evidence to support its occurrence in small sample sizes [65][66][67], these results remain controversial. Later investigations supported the notion of vertical transmission based on serological evaluations of RT-PCR-positive newborns (high levels of SARS-CoV-2-targeted IgM and inflammatory cytokines-IL6/IL10 [68][69][70][71][72][73]), amniotic fluid [70], and cord blood RT-PCR [74]. Recently, documentation of the SARS-CoV-2 genome on both sides of the placenta, maternal and fetal, apparently demonstrated transplacental transmission of SARS-CoV-2 [45].…”
Section: Discussionmentioning
confidence: 89%
“…Although initial reports on SARS-CoV-2 vertical transmission found no evidence to support its occurrence in small sample sizes [65][66][67], these results remain controversial. Later investigations supported the notion of vertical transmission based on serological evaluations of RT-PCR-positive newborns (high levels of SARS-CoV-2-targeted IgM and inflammatory cytokines-IL6/IL10 [68][69][70][71][72][73]), amniotic fluid [70], and cord blood RT-PCR [74]. Recently, documentation of the SARS-CoV-2 genome on both sides of the placenta, maternal and fetal, apparently demonstrated transplacental transmission of SARS-CoV-2 [45].…”
Section: Discussionmentioning
confidence: 89%
“…Of the included 58 studies, nine were carried out in the United States [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], six in Italy [ 46 , 47 , 48 , 49 , 50 , 51 ], five in Brazil [ 52 , 53 , 54 , 55 , 56 ], four in France [ 57 , 58 , 59 , 60 ], four in Iran [ 61 , 62 , 63 , 64 ], three in Germany [ 65 , 66 , 67 ], three in Spain [ 68 , 69 , 70 ], two in Portugal [ 71 , 72 ], two in Romania [ 73 , 74 ], two in Russia [ 75 , 76 ], one in Peru [ 77 ], Slovakia [ 78 ], Columbia [ 79 ], China [ 80 ], Turkey [ 81 ], Switzerland [ 82 ], Ireland [ 83 ], India [ 84 ], Canada [ 85 ], UK [ 86 ], Mexico [ 87 ], Singapore [ 88 ], Malaysia [ 89 ], B...…”
Section: Resultsmentioning
confidence: 99%
“…Of the included 58 studies, nine were carried out in the United States [37][38][39][40][41][42][43][44][45], six in Italy [46][47][48][49][50][51], five in Brazil [52][53][54][55][56], four in France [57][58][59][60], four in Iran [61][62][63][64], three in Germany [65][66][67], three in Spain [68][69][70], two in Portugal [71,72], two in Romania [73,74], two in Russia [75,76], one in Peru [77], Slovakia [78], Columbia [79], China [80], Turkey [81], Switzerland [82], Ireland [83], India [84], Canada [85], UK…”
Section: Resultsmentioning
confidence: 99%
“…Of the included studies, 25 studies reported assessment of the placenta, of these 18 were case studies (Alamar I 2020, Birindwa EK 2020, Ferraiolo A 2020, Grimminck K 2020, Kulkarni R 2020, Hsu AL 2020, Lv Y 2020, Palalioglu RM 2020, Pulinx B 2020, Rebello CM 2020, Shende P 2020, Sisman J 2020, Stonoga E 2020, Tang J 2020, Von Kohorn I 2020, Zaigham M 2020, 2 were retrospective case series (Liu W 2020, Masmejan S 2020, 3 were cohort studies (Fenizia B 2020, Ogamba I 2020, Oncel MY 2020 and 2 were a cohort and a case series specifically studying placental samples (Smithgall MC 2020, Zhang P 2020) (Supplementary file Table 4. Findings of studies reporting placenta analysis).…”
Section: Detection Of Virus In the Placenta Using Pcr And Immunostainingmentioning
confidence: 99%